PELESTARIAN TARI ZAPIN SEBAGAI SALAH SATU ATRAKSI WISATA DIKOTA PEKANBARU DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN - Pakpahan, Yemima Suka Cita; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The objective ot this research is as reminder for the local government, people andor all other parties to participate and preserve the cultural arts in the city of pekanbaruexpecially zapin dance. This research was conducted at the departement of culture andtourism, and also in shelomita studio in pekanbaru. To achive the objectivities of thisresearch the writer and descriptive qualitative analysis. In which she describe how tomaintain a traditional culture plus introducing the culture to foreign countries in order topreserve its exsistance as many young generations nowdays seems like forgrtting theirown traditional culture. The writer wrote he data based on the library books and directinformation from people who are able to provide accurate information relating to thisresearch tari zapin it self is one of the art culture that needs to be preserved as it can beone of the tourist attractions in pekanbaru city. The local goverment and the communityneed to get involved and paricipated in promoting this dance to young generation andforeign countries as to maintain its exsistance.Kewords : the role of Governent, the preservation of culture, torism preservation